Will Light Castle partners bring a positive change in the equity based impact investment for the marginalized agro entrepreneurs in the rural regions of Bangladesh? - Islam, Auitry Rutaba (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.